Mulheres negras no Candomblé: um estudo sobre a atuação política de duas Yalorixás no estado de São Paulo - Chaves, Tatiana Otoboni (2020)
This research aimed to investigate the visibility of the black woman inserted in the Candomblé. From the debate on racism, gender, politics and religion of African origin, the life trajectories of the Yalorixás Claudia of Oyá and Luciana of Oyá were researched. The research aims to observe and understand the trajectory of two black women who occupy the position of religious leaders. One research participant works on the border between the municipality of São Paulo and Diadema, in the Eldorado neighborhood and the other in the municipality of Guarulhos, in the Pimentas neighborhood, both located in Greater São Paulo. From the field research, the political actions of these characters in the communities in which they operate and their political actions in social movements, public policy forums, councils and NGOs were verified. The relevance of black women as a maintainer of memory and of African culture in the focus of Candomblé religion, an ancient and recent target of religious prejudices, violence and intolerance in Brazil